Expected Prescription Error (EPE) Scores of Cancer Drugs in Egypt: A New Method of Data Extraction from a Questionnaire Based Study (International Journal of Scientific Research and Management (IJSRM), 2017)
Registration Details Of The Current Study: The current study is a part of a research registered on www.clinicaltrial.gov NCT02630979. The study received approval from the Institutional Review Board (IRB) of the Clinical Oncology department. Faculty of Medicine, Ain Shams University in October 2015. Sources Of Support: There is no source of support of any type either financial or technical received by the authors of this study to implement this study. No source of funding from National Institutes of Health (NIH); Welcome Trust; Howard Hughes Medical Institute (HHMI); or other(s).